2017
DOI: 10.1038/mp.2017.85
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling DAPK1 from NMDA receptor GluN2B subunit exerts rapid antidepressant-like effects

Abstract: Several preclinical studies have reported the rapid antidepressant effects of N-methyl-D-aspartate receptor (NMDAR) antagonists, although the underlying mechanisms are still unclear. Death-associated protein kinase 1 (DAPK1) couples GluN2B subunits at extrasynaptic sites to regulate NMDAR channel conductance. In the present study, we found that chronic unpredictable stress (CUS) induced extracellular glutamate accumulation, accompanied by an increase in the DAPK1–NMDAR interaction, the high expression of DAPK1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 80 publications
(106 reference statements)
2
54
0
Order By: Relevance
“…To clarify whether ketamine's action to prevent mGlu 2/3 receptor agonist-induced hyperthermia is due to NMDAR inhibition, we assessed three distinct NMDAR antagonists: (i) (+)-MK-801, a noncompetitive NMDAR antagonist, which acts at the same phencyclidine (PCP)/ketamine site of the NMDAR; (ii) (±)-CPP, a competitive NMDAR antagonist; and (iii) Ro 25-6981, a GluN2B-specific NMDAR antagonist; we used doses known to exert putative antidepressant-relevant actions in rodents (15,33,(72)(73)(74)(75)(76) and to induce NMDAR inhibition-mediated behaviors (75,(77)(78)(79). Administration of these NMDAR antagonists did not prevent mGlu 2/3 receptor agonist-induced hyperthermia ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To clarify whether ketamine's action to prevent mGlu 2/3 receptor agonist-induced hyperthermia is due to NMDAR inhibition, we assessed three distinct NMDAR antagonists: (i) (+)-MK-801, a noncompetitive NMDAR antagonist, which acts at the same phencyclidine (PCP)/ketamine site of the NMDAR; (ii) (±)-CPP, a competitive NMDAR antagonist; and (iii) Ro 25-6981, a GluN2B-specific NMDAR antagonist; we used doses known to exert putative antidepressant-relevant actions in rodents (15,33,(72)(73)(74)(75)(76) and to induce NMDAR inhibition-mediated behaviors (75,(77)(78)(79). Administration of these NMDAR antagonists did not prevent mGlu 2/3 receptor agonist-induced hyperthermia ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, a single administration of the GluN2B acting NMDAR antagonist Ro 25–6981 decreases behavioral despair in the 24-hr forced-swim test [42, 47, 93, 94], novelty-suppressed feeding test [42, 47, 55], novelty-induced hypophagia [56] and reverses anhedonia following chronic mild stress [55]. Similarly, ifenprodil, another GluN2B-NMDAR antagonist, reverses chronic unpredictable stress-induced sucrose preference deficits and behavioral despair in rodents following a single administration [95]. Recently, it has been shown that ketamine might induce its acute (1-h) antidepressant actions via blockade of NMDAR-dependent burst activity in the lateral habenula neurons [96]; however, it remains to be determined whether this action of ketamine is responsible for the long-lasting antidepressant actions of the drug.…”
Section: Mechanisms Underlying Fast/rapid Onset Antidepressants Acmentioning
confidence: 99%
“…Finally, sub-chronic (5 days) administration of a 5-HT 2C antagonist [239], as well as partial activation of the GABA A receptor (via inhibition of GLO1) [179], increase BDNF protein levels in the mPFC and/or hippocampus of mice. In addition, administration of ketamine, GluN2-NMDAR antagonists, mGluR 2/3 antagonists and electroconvulsive shock reverse chronic stress-induced reduction in BDNF levels in the PFC [95, 198] and hippocampus [198, 310312] of rodents, suggesting that BDNF induction could be considered as a marker of rapid antidepressant efficacy. Short-term (6–48 h) sleep deprivation has been shown to both increase [303, 313] or decrease [314, 315] hippocampal BDNF levels in stress-naïve rats, and has been shown to restore decreased BDNF levels in the hippocampus following chronic stress [316].…”
Section: Downstream Pathways Involved In Rapid Antidepressant Actionsmentioning
confidence: 99%
“…In 2009, a novel and selective DAPK family inhibitors were identified based on oxazol‐5‐one core by structural based virtual screening . Representative examples are shown in Figure .…”
Section: Dapks Inhibitorsmentioning
confidence: 99%